Simulation of Viscous Flows Around a Moving Airfoil by Field Velocity Method with Viscous Flux Correction (Advances in Applied Mathematics and Mechanics, 2012)
Based on the field velocity method, a novel approach for simulating unsteadypitching and plunging motion of an airfoil is presented in this paper. Responsesto pitching and plunging motions of the airfoil are simulated under differentconditions. The obtained results are compared with those of moving gridmethod and good agreement is achieved. In the conventional field velocity method,the Euler solver is usually used to simulate the movement of the airfoil. However,when viscous effect is considered, unsteady Navier-Stokes equations have to besolved and the viscous flux correction must be taken into account. In this work, theviscous flux correction is introduced into the conventional field velocity methodwhen non-uniform grid speed distribution is occurred. Numerical experiments forthe flow around NACA0012 airfoil showed that the proposed approach can wellsimulate viscous moving boundary flow problems.